PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA DI TEMPAT OLAH SAMPAH SETEMPAT WERDI GUNA DESA GUNAKSA KABUPATEN KLUNGKUNG - Dedi Wiriastika, I Putu; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i01.p6, 2022)
The use of renewable energy is a solution in the application of clean and environmentally friendly energy, one of which is the use of solar power with the PLTS system. In this study, the PLTS system planned at TOSS Werdi Guna is a PLTS-On Grid system without a battery with a ground mounted installation, the aim is to reduce the cost of electricity bills. PLTS planning at TOSS Werdi Guna has a capacity of 32.6kWp with a number of 86 modules and uses 1 inverter unit with a capacity of 33kW. The energy production produced by PLTS for a year is 52,955kWh. The total investment cost required is IDR 580,469,095 with a payback period of 7 years and 4 months.